Urban regeneration - Roberts, Peter W.; Sykes, Hugh; Granger, Rachel (Sage, 2017)
"Providing students and practitioners with a detailed overview of the key theoretical and applied issues, this book is a comprehensive and integrated primer on regeneration. The various chapters: review the history and context of urban regeneration; consider funding implications; look at environmental, social and community issues, as well as employment, education and training; focus on managing urban regeneration; consider land use issues; and discuss monitoring and evaluation. The book concludes with a comparative analysis, with examples from America and Europe, and a discussion of future trends. The book represents the first systematic overview of urban regeneration in one volume and is set to become the standard reference." --Publisher.